32 Addressing efficiency of clinical information delivery in cardiology wards: experience from a quality improvement project on echocardiography reporting. (16th November 2020) - Martinuzzi, Michela; Ramji, Saajan; Raj, Siddarth; Vuyyuru, Ramabala
Abstract : Echocardiography is a key diagnostic procedure, but delays or requests overload might compromise its contribution to the clinical decision process. This project aimed at speeding the availability of echocardiograms results by applying two strategies: 1) Introducing a provisional report (PR) to be delivered immediately to doctors; 2) Reducing the number of referral requests by changing the triage process. Baseline data were gathered during a 9-week period. The first intervention cycle applied strategy1 by introducing a PR given verbally by echocardiographers to doctors which contained key clinically relevant findings. Rate of uptake of the PR and time from echocardiogram completion to PR availability were monitored during the following 6 weeks. Strategy2 was implemented 4 weeks after the conclusion of cycle1 and introduced triaging by cardiologists. They determined echocardiogram appropriateness which we expected to reduce the number of overall referrals. Number of requests and time from referral to echocardiogram completion to report availability were monitored during the following 6 weeks. Semi-structured questionnaires proposed at the end of both cycles explored participants' views of the effects of the changes. Cycle1 resulted in a 78% reduction of the median time used to get relevant information to clinicians. However, PR uptake varied across the observation window reaching at best 40%. Cycle2 resulted in a 40% reduction in the median number of referrals per week and in a 31% reduction of the median time needed from referral to full report. 62% of the doctors reported they noticed improvements in reporting speed after cycle1, which increased to 71% after cycle2. 87% of participants felt strategy1 and 71% felt strategy2 improved patient timely discharge. Significant improvements in the reporting times of key clinical information can be achieved; however, sustainability and staff engagement are key factors that can influence adherence and long-term outcomes.